Predicting Low Toxicity and Scalable Solvent Systems for High‐Speed Roll‐to‐Roll Perovskite Manufacturing. Issue 3 (5th November 2021) - Swartwout, Richard; Patidar, Rahul; Belliveau, Emma; Dou, Benjia; Beynon, David; Greenwood, Peter; Moody, Nicole; deQuilettes, Dane; Bawendi, Moungi; Watson, Trystan; Bulovic, Vladimir
Abstract : Printed lead‐based perovskite photovoltaics (PV) have gained interest due to their potential to be manufactured with scalable roll‐to‐roll techniques. In industrial scale‐up, toxicity of inks can constrain roll‐to‐roll manufacturing due to the added cost of managing toxic effluents. Due to solvent toxicity, few perovskite solution chemistries in published works are scalable to gigawatt production capacity at low cost. Herein, it is shown that for scalable PV production, the use of aprotic polar solvents should be avoided due to their overall toxicity. Compliance with worldwide worker safety regulations for solvent exposure limits could require additional air handling requirements for some solvents, which in turn would affect cost‐effectiveness. It is shown that costs associated with handling of hazardous substances can be significant and estimate an added cost of ¢3.7/W for dimethylformamide (DMF)‐based inks. To solve this problem, a new perovskite ink solvent system is developed that is composed entirely of ether and alcohol, which has an effective exposure limit 14× higher than DMF, making it suitable for industrial coating processes. It is shown that the new ink solvent system is capable of fabricating high‐efficiency perovskite solar cells processed in 1 min on a standard roll‐to‐roll system. Abstract : Herein, it is demonstrated that the regulatory requirement to limit exposure of solvent vapors generated from ink‐based coating process can be economically limiting for perovskite photovoltaics. A technoeconomic framework and solubility model was developed to guide ink development which leads to the development of an ink system with a 12× higher exposure limit than what is commonly used in the field.